TYPOLOGY OF EX-WIFE’S RESPONSE IN SIWALAN PEKALONGAN: SOCIO-LEGAL ANALYSIS OF POST-DIVORCE CHILD SUPPORT - Ali Muhtarom; Naila Umdah Zuhaidah; Siti Qomariyah (JURNAL HAKAM, 2026)
This study examines the phenomenon of abandonment of post-divorce child support in Siwalan District, Pekalongan Regency, which is contrary to Law No. 1 of 1974 and Islamic law. Although regulations expressly impose maintenance obligations on fathers, empirical reality shows that there is a default that has a significant impact on the welfare of children. This qualitative research with a field research approach aims to formulate the typology of ex-wife's response and analyze the sociological implications caused. Data were collected through in-depth interviews, observations, and documentation of single mothers at the study site. The results of the study classified the response of ex-wives into three typologies: 1) Legalistic-Active (ex-wives have a conscious and firm attitude to the point of using state instruments to force the fulfillment of child support rights); 2) Adaptive-Independent (the legal awareness and culture of ex-wives tend to be low, take a pragmatic attitude based on economic independence, and avoid social stigma); 3) Negotiative-Persuasive (Ex-wives use social capital and family relationships to claim child support rights). This variation in response is influenced by legal awareness, social support, and pragmatic rationality. The implications of this typology suggest that financial independence increases the double burden for mothers, while dependence on ex-husbands creates uncertainty. The legal route provides certainty but risks escalating family conflicts. Fundamentally, this irregularity of livelihood hinders children's growth and development both physically, educationally, and socially. A balance between financial support and emotional stability is key in minimizing the negative impact of post-divorce. This research contributes to mapping the legal behavior of communities at the rural level regarding child support. Through the formulation of three response typologies (Legalistic-Active, Adaptive-Independent, and Negotiable-Persuasive), this study offers a new perspective for family law enforcement that is more responsive to social realities and the best interests of the child